2015
DOI: 10.1186/s40409-015-0021-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection and antimicrobial resistance of Pseudomonas aeruginosa from houseflies (Musca domestica) in Iran

Abstract: BackgroundPseudomonas aeruginosa is a common bacterium that can cause disease in humans and other animals. This study was conducted to screen for molecular detection and antimicrobial-resistant P. aeruginosa in Musca domestica in different locations in the Iranian provinces of Shahrekord and Isfahan.MethodsMusca domestica were captured by both manual and sticky trap methods, during the daytime, from household kitchens, cattle farms, animal hospitals, human hospitals, slaughterhouses and chicken farms at random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 34 publications
2
16
0
1
Order By: Relevance
“…A baumannii is one of the commonly isolated non-fermenting bacteria in human specimens, especially of nosocomial origin after Pseudomonas aeruginosa. Its infections are uncommon but, when they occur, it is usually associated with organ systems with high fluid content eg respiratory tract, CSF, peritoneal fluid and urinary tract (18)(19)(20). Just as observed in this study, A baumannii was detected from all sample groups from organs with fluid content including blood, urine and CSF.…”
Section: Discussionsupporting
confidence: 79%
“…A baumannii is one of the commonly isolated non-fermenting bacteria in human specimens, especially of nosocomial origin after Pseudomonas aeruginosa. Its infections are uncommon but, when they occur, it is usually associated with organ systems with high fluid content eg respiratory tract, CSF, peritoneal fluid and urinary tract (18)(19)(20). Just as observed in this study, A baumannii was detected from all sample groups from organs with fluid content including blood, urine and CSF.…”
Section: Discussionsupporting
confidence: 79%
“…and Enterococci to name just a few, are also important causes of diseases in humans (including nosocomial infection). Furthermore, several studies reported bacteria that were resistant to multiple antibiotics including E. coli (20,35,36), Klebsiella pneumoniae [ 15 , 47 ] and Pseudomonas aeruginosa [ 15 , 19 , 48 ]. Most of the antibiotic resistant bacteria were isolated from flies caught in and around hospital environments and animal farms (where there is an extensive use of antibiotics as growth promoters) [ 15 , 17 20 , 49 , 50 ], suggesting that house flies may also play a role in the dissemination of antibiotic resistant bacteria to different environments [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, house flies living in and around human habitats harbor a variety of pathogenic and nonpathogenic agents from several taxa including antibiotic-resistant bacteria (Bunchu et al 2014;Chaiwong et al 2014;Cohen et al 1991). Types of pathogens, carried by flies, are determined by the people and animals present in where flies are found, as well as the extent to which antibiotics are utilized in any given area (Nazari et al 2017;Davari et al 2010;Doud and Zurek 2012;Hemmatinezhad et al 2015;Kassiri et al 2015;Wang 2013;Zurek and Ghosh 2014). Moreover, house flies living in the hospital environment may be associated with the spread of nosocomial infections (Hemmatinezhad et al 2015;Sarwar 2015).…”
Section: Introductionmentioning
confidence: 99%